Pengabdian Berbasis Teknologi dalam Menunjang Pengalaman dan Interaksi Pengunjung Terhadap Destinasi Wisata Melalui Aplikasi AR Gamification - Wiguna, I Komang Arya Ganda; Sanusi, Rikcy; Sudipa, I Gede Iwan; Semadi, Ketut Ngurah; Iswara, Ida Bagus Ary Indra; Udayana, I Putu Agus Eka Darma; Aristana, Made Dona Wahyu (FKIP, Universitas Palangka Raya, 2023)
Technology's role in tourism can have a positive effect on attracting tourists. In providing solutions to non-optimal media in supporting alternative entertainment and services for tourists, the service activity's goal of integrating augmented reality (AR) in tourism has given rise to the concept of AR gamification, in which game elements are integrated into the tourist experience to create a more enjoyable and interactive experience. Potential users are assisted in comprehending and optimizing their use of AR gamification applications. The implementation of augmented reality games at The Sila's Agrotourism benefited from the active participation of collaborators in all PKM activities. The results demonstrated that the use of augmented reality (AR)-based interactive games in tourist destinations enhances the destination's appeal and encourages visitor participation in associated activities. The implementation of augmented reality technology makes the tourist experience at The Sila's Agrotourism more engaging and enjoyable for guests, which has positive repercussions for boosting tourist attraction and satisfaction.